Understanding Islamic Finance - Ayub, Muhammad (Wiley Finance, 2007)
This book is an important text for all those who work in banks and financial institutions entering this particular market with a commitment to building islamic financial solutions, but it also essential reading for undergraduate and postgraduate students of Islamic finance